New species and records of Macratriinae LeConte, 1862 (Coleoptera: Anthicidae) from the Americas with five new descriptions - Telnov, Dmitry (Zootaxa, 2023)
Descriptions of the following five new species of Macratriinae LeConte, 1862 are presented based on the material mainly from the Natural History Museum London: Macratria bugle sp. nov. (Panama), M. conlei sp. nov. (Ecuador), M. florsavichi sp. nov. (Panama), M. guaymi sp. nov. (Panama) and M. tiriyo sp. nov. (Guyana / Suriname). New distribution records for the Central American Macratria obsoleta Champion, 1890 are also provided.